Regulation of the Assembled Structure of a Flexible Porphyrin Derivative Containing Tetra Isophthalic Acids by Coronene or Different Pyridines - Ma, Lin (Langmuir : the ACS journal of surfaces and colloids, 2022)
Based on previous research, a new coassembly formed by a porphyrin derivative (IPETPP), which contains a flexible substituent of m-phthalic acid, is observed with coronene (COR) molecules at a higher concentration. Besides, a fresh IPETPP self-assembly formed at a lower concentration and another new coassembly with COR molecules are obtained. Moreover, the addition of a series of bipyridines alters the diamond arrangement of IPETPP, which enhances the stability of the two-component structures. It is unprecedented that bipyridine derivatives break intermolecular hydrogen bonds containing m-phthalic acid substituents. All the coassemblies are investigated by scanning tunneling microscopy on a highly oriented pyrolytic graphite. Combined with density functional theory, the formation mechanism of the assembled structures is revealed. These results would contribute to understanding the interfacial crystal behaviors and probably provide an efficient pathway to regulate the binary structures